2022
DOI: 10.3201/eid2809.220222
|View full text |Cite
|
Sign up to set email alerts
|

International Spread of Multidrug-Resistant Rhodococcus equi

Abstract: R hodococcus equi is a soilborne aerobic actinomycete bacterium that infects animals and humans. Human infections are opportunistic, zoonotic in origin, and considered to be linked to exposure to farm environments (1-3). Although clinical R. equi infections are relatively rare in most animal species, foals are commonly affected, and incidence is often high in horse farms in equine breeding countries (4). Long courses of rifampin and a macrolide is the mainstay therapy for foal rhodococcosis. This treatment has… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…We have now detected pRErm46 in other R equi genomotypes (either associated with different rpoB mutations – eg, S531L, S531Y – or without them), indicating that the pRErm46 plasmid has begun to spill across the equine‐associated R equi population 15,21 . pRErm46 plasmid loss with macrolide resistance linked to transposition of Tn RErm46 onto the host genome has also been detected in some MDR‐RE 2287 sublineages 15,20 …”
Section: Characterisation Of Mdr‐rementioning
confidence: 78%
See 3 more Smart Citations
“…We have now detected pRErm46 in other R equi genomotypes (either associated with different rpoB mutations – eg, S531L, S531Y – or without them), indicating that the pRErm46 plasmid has begun to spill across the equine‐associated R equi population 15,21 . pRErm46 plasmid loss with macrolide resistance linked to transposition of Tn RErm46 onto the host genome has also been detected in some MDR‐RE 2287 sublineages 15,20 …”
Section: Characterisation Of Mdr‐rementioning
confidence: 78%
“…Interestingly, despite the high horizontal transferability of pRErm46, the vast majority of the macrolide‐resistant R equi isolates belong to the same strain, a specific clonal subpopulation named MDR‐RE ‘2287‘ (after the designation of the prototype isolate kept in our laboratory in Edinburgh, PAM2287) 15,17,19,20 …”
Section: Characterisation Of Mdr‐rementioning
confidence: 99%
See 2 more Smart Citations
“…Apart from the potential long-term selection of MDR R. equi and its detrimental effect on equine health, the accumulation of antimicrobial residues establishes constant antimicrobial pressure for the enhancement and spread of MDR pathogens with the potential to threaten humans and other animals through contact or the consumption of contaminated food and water [ 36 ]. Previous studies have shown that antimicrobial-resistant R. equi have spread internationally [ 37 ], demonstrating the potential global impact of even a single event of AMRGs acquisition [ 38 ]. Moreover, the accumulation of residues can have ecotoxicological effects, interfering with the normal microbiome of soils and plants and affecting agricultural yield [ 39 ].…”
Section: Discussionmentioning
confidence: 99%